Analysis of The Role of Biotic Components in Ecosystem Equilibrium Through Aquaponic Modeling Using Covariate Analysis - Natalia, Grace; Lo, Keiko Vianna; Valencia, Sharleen (Westscience Press, 2025)
Overusing pesticides has caused numerous problems in the agricultural sector and led to mutagenic effects in fish. Additionally, land conversion across Indonesia is a major challenge for farmers. Farmers have adopted an aquaponic system by combining catfish and hydroponic rice cultivation to address this. This method has been widely used in Indonesia; however, it still lacks a scientific benchmark. This research aims to observe changes in biotic component behavior after degradation of bacterial strains, namely Lactobacillus, Nitrobacter, and Photosynthetic Bacteria. Through this, we will analyze the interaction between catfish and paddy using a parametric ANCOVA assay. The results show that the use of bacterial strains significantly affects the catfish growth in terms of length and weight. However, the correlation between the growth of catfish and paddy is not significant. While the well-being of catfish contributes to better paddy growth, the absence of catfish does not negatively impact paddy growth, as catfish are not the primary source of nutrients required by the paddy.